Receiver-based data forwarding in vehicular ad hoc networks - Husain, K. (Institute of Electrical and Electronics Engineers Inc., 2017)
Efficient Routing in Vehicular Ad Hoc Networks (VANETs) is one of the main challenges faced while providing reliable communication in the vehicular environment. Routing approaches that make routing decisions on the fly during data transmissions are much more suitable for the high mobility and variable density conditions present in the vehicular environment. Receiver-based data forwarding is one such routing approach where the receiving nodes decide whether or not to forward the data packet. However, existing work on receiver based schemes in VANET highlight two issues. Firstly, the unwanted multiple path formation when the receiving nodes are not in transmission range of each other. Secondly, most of the existing receiver-based data forwarding schemes make use of forwarding zone concept which limits the potential contenders thereby reducing the chances of optimal path selection. In this paper, we propose the idea of a receiver-based data forwarding scheme that addresses the above mentioned issues. The proposed scheme avoids multiple path formation by making use of feedback approach. Also, the receiving node decides whether or not to contend for the forwarding right based signal to interference plus noise ratio (SINR) and geographic progress rather than using the forwarding zone concept. After briefly discussing the proposed scheme, we then highlight the possible issues that require further investigation. © 2016 IEEE.